Peningkatan Keamanan Data dengan Kriptografi Modern pada Sistem Operasi - Rakhmadi Rahman; Khumaedi Khumaedi; Nugrah Surya Pratama (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
In the current digital era, data security is a top priority for individuals, organizations, and businesses. Data is considered a valuable asset that needs to be protected from various security threats, especially in operating systems where data is stored (data at rest) and transmitted (data in motion) through networks. This research aims to enhance data security by implementing modern cryptographic methods. The cryptographic methods used include RC4, AES, and WPA3. Penetration testing is conducted to evaluate the effectiveness and efficiency of each cryptographic method. The research results show that the implementation of modern cryptography provides an additional layer of security against security threats to data in motion and data at rest within the operating system.